UTILIZING MICROSOFT MATHEMATICS IN TEACHING AND LEARNING CALCULUS - Rina Oktaviyanthi; Yani Supriani (Journal on Mathematics Education, 2015)
The experimental design was conducted to investigate the use of Microsoft Mathematics, free software made by Microsoft Corporation, in teaching and learning Calculus. This paper reports results from experimental study details on implementation of Microsoft Mathematics in Calculus, students’ achievement and the effects of the use of Microsoft Mathematics on students’ attitudes in relation to such experience. Two classes of the students from the first year student in Universitas Serang Raya were participated in the study. This study found that students who taught by using Microsoft Mathematics had higher achievement and has a positive effect on students’ confidence of mathematics.Keywords: Calculus, Educational Technology, Mathematics Education, Microsoft Mathematics, Technology Application DOI: dx.doi.org/10.22342/jme.61.63